2020
DOI: 10.7498/aps.69.20191689
|View full text |Cite
|
Sign up to set email alerts
|

Discrete modulation continuous-variable quantum key distribution based on quantum catalysis

Abstract: Compared with discrete variable quantum key distribution (DVQKD), continuous variable (CV) QKD has high security bit rate and other advantages, which, however, are slightly insufficient in secure transmission distance. In addition, the application of quantum catalysis has significantly improved the performance of Gaussian modulated (GM) CVQKD, especially in secure transmission distance. Recently, the application of quantum catalysis has significantly improved the performance of GM-CVQKD. However, whether it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…For example, the parity detection has been proved to be an optimal detection for linear phase estimation in lots of schemes [27,51]. Compared with both intensity and parity detections, however, homodyne detection can be easily realized with current technologies, thereby playing a key role in the field of continuous-variable quantum key distribution (CV-QKD) [52][53][54][55][56]. Therefore, in our scheme the homodyne detection is employed on mode a at one of output port to estimate the phase parameter φ, where the detected variable is the amplitude quadrature X, i.e.,…”
Section: Phase Sensitivity Via Homodyne Detectionmentioning
confidence: 99%
“…For example, the parity detection has been proved to be an optimal detection for linear phase estimation in lots of schemes [27,51]. Compared with both intensity and parity detections, however, homodyne detection can be easily realized with current technologies, thereby playing a key role in the field of continuous-variable quantum key distribution (CV-QKD) [52][53][54][55][56]. Therefore, in our scheme the homodyne detection is employed on mode a at one of output port to estimate the phase parameter φ, where the detected variable is the amplitude quadrature X, i.e.,…”
Section: Phase Sensitivity Via Homodyne Detectionmentioning
confidence: 99%
“…More strikingly, the single-phase estimation with the QCRB in the presence of noisy environments, e.g., photon loss [17][18][19], phase diffusion [20,21], and thermal noise [22,23], can be tackled using the variational method [17,20] pro-posed by Escher, greatly promoting the practical applications of quantum metrology [24][25][26]. On the other hand, extending toward the multiple phase estimation with the QCRB has attracted considerable interest more recently, thereby resulting in the potential applications [27][28][29][30][31][32][33][34], such as quantum-enhanced sensor network [29][30][31][32] and optical imaging [33,34]. Moreover, in order to improve the precision of multiple-phase estimation, multimode NOON (or NOON-like) states [35][36][37][38][39], generalized entangled coherent states [40] and multimode Gaussian states [41] have been considered, even in the presence of noisy environment [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…They found that for all attained states, only the photon-subtracted and photon-addedthen-subtracted states can perform better than the original TMSV in terms of the entanglement improvement. In addition to these conventional non-Gaussian operations, the usages of the quantum catalysis [20,24] and the quantum scissor [19,32] are other feasible ways to improve the nonclassicality and entanglement of quantum states, which makes them play an important role in realizing the long-distance quantum communication [33][34][35].…”
Section: Introductionmentioning
confidence: 99%